Detrimental effects detected in exfoliated buccal cells from anesthesiology medical residents occupationally exposed to inhalation anesthetics: An observational study - Braz, Mariana Gobbo [UNESP]; Souza, Kátina M. [UNESP]; Lucio, Lorena M.C. [UNESP]; Di Renzo, Giulia C.C. [UNESP]; Feliciano, Luciana M. [UNESP]; Marcondes, João Paulo C. [UNESP]; Chen, C.-Y. Oliver; Braz, José Reinaldo C. [UNESP]; Braz, Leandro Gobbo [UNESP] (Elsevier, 2018)
Operating room professionals are scarcely aware of their individual occupational exposure to waste anesthetic gases (WAGs). Medical residents spend several hours per day in operating rooms and consequently experience occupational exposure to WAGs. Considering that no studies have yet evaluated the potential toxicity in medical residents exposed to WAGs using the buccal micronucleus cytome (BMCyt) assay, this pioneering study aimed to compare the BMCyt assay markers, including DNA damage, cell proliferation, and cell death in the exfoliated buccal cells of surgery and anesthesiology residents occupationally exposed to WAGs. The study enrolled a total of 60 physicians, including internal medicine residents (unexposed group), and residents from surgery and anesthesiology programs who were occupationally exposed to sevoflurane, isoflurane and nitrous oxide. WAGs were measured, and the mean values were higher than the international recommendation. The anesthesiology residents (high exposure) showed statistically significant lower frequencies of basal cells, and statistically significant higher frequencies of micronuclei, karyorrhexis, pyknosis, and differentiated cells than did the unexposed group; karyolysis frequencies were significantly higher in anesthesiology residents than were those in the unexposed group or in surgical residents (low exposure). The findings suggest a genetic risk for young professionals exposed to WAGs at the beginning of their careers. Thus, exposure to high WAGs concentrations leads to impairment of the buccal cell proliferative potential, genomic instability and cell death, especially in anesthesiology residents, demonstrating an early impact on their health.
Keywords: Anesthetic gases; Buccal mucosa; Genome instability; Occupational exposure